Forecasting Starbucks Indonesia Share Prices with Methods ARIMA: Memprediksi Harga Saham Starbucks Indonesia dengan Metode ARIMA - Fellya Naza Nurcahyani; Septiana Putri Milasari; Indah Manfaati Nur (Department of Sains Data UNIMUS Universitas Muhammadiyah Semarang, 2025)
Starbucks is the largest coffee shop company in the world from the United States. This increase has become a trend in drinking coffee consumption among young people in a lifestyle while discussing. This indicates that the increase in the number of Starbucks stores is one of the drivers of Starbucks share prices among investors. Starbucks shares have the code SBUX as the issuer code. Starbucks Corporation is a coffee company and global coffeehouse chain. Satrbucks is an international company (MNCs) that anticipates various risks. The ARIMA forecasting method is different from other forecasting methods. This method uses an iterative approach to identify the most appropriate model from all possible existing models and this model can use all types of data. The ARIMA method was chosen for this research because this method is very suitable for short-term forecasting, where the products produced by the PT have a short expiration date. The result of the MAPE value is 3.218%, which means the accuracy is good because it is less than 10%.